A New Helmetiid Arthropod from the Early Cambrian Chengjiang Lagerstätte, Southwest China. (March 2014) - Zhao, Fangchen; Hu, Shixue; Zeng, Han; Zhu, Maoyan
Abstract : A new arthropod, Haifengella corona new genus new species is described from the early Cambrian Chengjiang Lagerstätte (Series 2, Stage 3), Yunnan Province, southwest China. It is readily assignable to helmetiida based on gross morphology of the tergum. The new helmetiid is unique in having the marginal spines extending over one-third of the total body width. The weakly sclerotized tergum consists of six thoracic tergites with edge-to-edge tergite articulations. The sub-trapezoidal cephalic shield has a pair of long spines projecting from each posterolateral corner. A prehypostomal sclerite (anterior sclerite) recesses in the anterior margin of the cephalic shield, and a pair of bulges that are close to the prehypostomal sclerite in the cephalic shield are presumed to be the position of ventral eyes. Each of the thoracic tergites exhibits a pair of long spines projecting from the posterolateral corners. The semicircular pygidium carries one terminal spine and two pairs of lateral spines.